Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1021/jacs.1c07518
|View full text |Cite
|
Sign up to set email alerts
|

Grain Boundary Engineering with Self-Assembled Porphyrin Supramolecules for Highly Efficient Large-Area Perovskite Photovoltaics

Abstract: Grain boundary management is critical to the performance and stability of polycrystalline perovskite solar cells (PSCs), especially large-area devices. However, typical passivators are insulating in nature and limit carrier transport. Here, we design a supramolecular binder for grain boundaries to simultaneously passivate defects and promote hole transport across perovskite grain boundaries. By doping the monoamine porphyrins (MPs, M = Co, Ni, Cu, Zn, or H) into perovskite films, MPs self-assemble into supramo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
95
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(96 citation statements)
references
References 43 publications
1
95
0
Order By: Relevance
“…We note that 1.19 V is among highest V OC reported so far in PSCs with an active area larger than 1 cm 2 to the best of our knowledge. [42][43][44][45][46][47] This record high V OC in a large-area device (PCE > 22%) could be attributed to the highquality and pinhole-free target-2 film with large grain size as well as the large V bi and low charge transport resistance discussed above. The photovoltaic parameter of large-area devices (area > 1 cm −2 , PCE > 22%) reported in literature have been summarized in Table S6, Supporting Information.…”
Section: Resultsmentioning
confidence: 99%
“…We note that 1.19 V is among highest V OC reported so far in PSCs with an active area larger than 1 cm 2 to the best of our knowledge. [42][43][44][45][46][47] This record high V OC in a large-area device (PCE > 22%) could be attributed to the highquality and pinhole-free target-2 film with large grain size as well as the large V bi and low charge transport resistance discussed above. The photovoltaic parameter of large-area devices (area > 1 cm −2 , PCE > 22%) reported in literature have been summarized in Table S6, Supporting Information.…”
Section: Resultsmentioning
confidence: 99%
“…[15][16][17] Meanwhile, the traps are also the invasion sources of water and oxygen, resulting in the rapid degradation of the perovskite grains, and then reducing the stability of the devices. [18,19] Surface passivation atop perovskite films is a proven significant strategy to reduce non-radiation recombination and improve interface contact. [20][21][22][23][24][25] Snaith et al made pioneering work taking advantage of iodopenta-fluorobenzene (IPFB) to passivate excess iodide ions (I À ) on the surface of perovskite films through supramolecular halogen bonding interactions, thus reducing surface defects and improving device performance.…”
Section: Introductionmentioning
confidence: 99%
“…[ 15–17 ] Meanwhile, the traps are also the invasion sources of water and oxygen, resulting in the rapid degradation of the perovskite grains, and then reducing the stability of the devices. [ 18,19 ]…”
Section: Introductionmentioning
confidence: 99%
“…[13] Cao and co-workers demonstrated that monoammonium porphyrin assisted PSCs to achieve a high PCE by controlling the crystallization, passivating defects, and/or promoting hole transport when embedded into the perovskite film. [20,[25][26][27] Cao's group also found that porphyrin with thiol could coordinate with Pb defects and help PSCs to get a better efficiency by treating the surface of perovskite film. [28][29][30] Porphyrin with other functional groups also shown great potential in improving PSCs [24] or OPV/PSCs [31] efficiency.…”
Section: Introductionmentioning
confidence: 99%